Icelandic immigrant identity – generational dissonance and connections to home - Sverrisdottir, Anna Margret (2022)
In the late 19th and early 20th century, large waves of Icelanders emigrated from the island and journeyed West to the Americas. The makeup of this emigrating population was balanced between women and men, laying the foundations for families where Icelandic heritage would be disseminated through two conjoined and cohesive channels, the mother and the father. Today, in the United States, immigration from Iceland continues, and many of the descendants of the original community still actively engage with their heritage. These heritage interactions happen both in the home and within heritage-based organizations. The organizations function as a communal space of familiarity and connection for all, whether they are a new immigrant or descendant. This research interacts with these spaces, asking how and what heritage stayed as the population grew more distant to their history in Iceland, and was challenged by ideas of ‘Americanizing’ as to better fit in. The analysis reveals strong connections to larger multi-family events, foods, and heritage language as strong indicators for feeling connected to one’s heritage. Furthermore, it speaks to the implications of how increased access to travel and new-found or re-kindled connections to people within Iceland, or in the Icelandic American community, has created a foundation for the diaspora to morph into a transnational community, which was not possible at the time of the first waves. For this research 27 interlocutors were interviewed, most of which belonged to or have participated in events with the Hekla Club in Minnesota, the oldest Icelandic heritage organization in the United States. Both old immigrants, 2nd generation and beyond, as well as new immigrants, 1st and 1.5 generation, were interviewed for the purpose of this research; interviews therefore conducted in Icelandic and English, as well as a mixture of both. This was done to find balance in the researcher’s own experiences as an immigrant. Using the researcher’s own story of immigration, and the story of their ...